Online Marketing Management of Processed Fish in Kedungjaya Kedawung Village, Cirebon - Cucum Novianti; Misbahussurur; Faozah; Inez Noviyani; Khodijah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study aims to determine and analyze Tristarfish's online marketing communication strategy on Instagram, including planning and implementation results in increasing sales of processed Tristarfish fish products. The methods used are observation, in-depth interviews and documentation. The analysis technique used in this research is an interactive model of analysis or interactive analysis (Miles & Huberman, 1992). The research results show that Instagram accommodates existing components in marketing communication strategies, such as providing consumer data to validate segmentation, targeting and positioning as well as being research material in determining the production of Instagram marketing content. The implementation of marketing of processed Tristarfish fish on Instagram by the @tristarfish.crb account is also carried out by implementing a marketing mix which includes 4Ps which include Product, Price, Place and Promotion. In terms of price, processed Tristarfish fish products are packaged in the cheapest packaging, namely IDR 10,000 to IDR 28,000 so that consumers from the lower middle class can still afford processed Tristarfish fish products. In terms of service or access, Tristarfish fish processing has provided one outlet and serves purchases using gofood or grabfood services so that consumers do not have to come to the outlet but can simply buy from home via the gofood or grabfood application.